Tarascon pocket pharmacopoeia for nurses : 2012 classic for nurses 2026-02-16T01:20:54+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Rockstraw, Leland J.; Donnelly, Gloria F. (Jones & Bartlett Learning, 2012)

(untitled)
Contains a listing of drugs most commonly administered by bedside nurses. Nursing implications are included for each drug with tips on administration and patient education